Predicting Medication Persistence to Buprenorphine Transdermal System. Issue 2 (20th January 2014) - Pergolizzi, Joseph V.; Ben‐Joseph, Rami; Chang, Chun‐Lan; Hess, Gregory
Abstract Objectives Persistence, the duration a patient remains on therapy, in chronic, symptomatic conditions plays an important role in therapy effectiveness. Understanding the duration and patient factors associated with prescribed medication persistence is, therefore, an important step toward better treatment and health outcomes for patients. In the following study, an analysis of such factors associated with buprenorphine transdermal system (BTDS) persistence was conducted utilizing a large US private practitioner and pharmacy claims database and is herein reported. Methods Patients aged ≥18 years initiating BTDS during January 1, 2011—November 30, 2011 were identified in the IMS Private Practitioner Medical Claims and Pharmacy Claims databases. An index date was defined as the first prescription of BTDS during the studied interval. During the preindex period, Charlson Comorbidity Index (CCI), chronic pain‐related conditions, and prior medication use were assessed. Concomitant medications and various treatment patterns (eg, last dose strength and dose adjustments) were assessed in the postindex 6‐month period. Persistence was measured as the duration of BTDS from initiation to the 1st >28‐day refill gap in the postindex 6‐month period. Descriptive statistical and survival analysis was used to assess the predictors of BTDS persistence. Results During the study period, 10, 457 patients newly treated with BTDS were identified. Patients' mean (±SD) age was 54.5 (±15.2) years; 69.9% were women, and the mean (±SD) CCI was 1 (±1.4). Utilizing a hierarchical approach, patients were separated into different cohorts based on the initial analgesic prescription identified during postindex period with 91.7%, 34.7%, and 59.0% of the patients using opioids, NSAIDs and adjuvant analgesics, respectively. Multivariate regression analyses showed that patients with prior opioid and adjuvant analgesic use were 21% and 5% less likely to discontinue BTDS (P < 0.05), respectively, as compared to patients not using these agents. Patients with concomitant use of adjuvant analgesics were 15% less likely to discontinue therapy (P < 0.05) as compared to patients without concomitant use of these agents. Long‐term BTDS persistence was also observed in patients who had a dose change or a last dose strength >5 mcg/hour. Sensitivity analyses for those with 30‐day prior opioid use and patients with ≥2 claims of BTDS confirmed these findings. Conclusions Prior and concomitant use of adjuvant analgesics, prior use of opioids, and dose adjustments were associated with significantly longer persistence among patients initiating BTDS. The results suggest that patients are less likely to discontinue BTDS early if practitioners account for prior treatment history and dose titration.